THE FUNERAL CONTEXTS AND ARCHAEOLOGICAL MATERIALS OF THE HUACA CONCHA - Echevarría López, Gori Tumi (2015)
Follow a research project of archaeological materials, the authors develop the inventory, classification and ordering of archaeological artifacts from the monument Huaca Concha, that were recovered from 1989 to 1994 and later deposited in the School of Archaeology of the San Marcos University. The main objective of the study consisted of the identification and reintegration of various funerary contexts rescued from Huaca Concha, that were being reorganized and stored by material items in the deposits of the school of archeology. This work also helped identify moments of material collection, responsible for recoveries and especially additional collections of cultural materials relevant to the history and the historical understanding of this archaeological site.